2021
DOI: 10.48550/arxiv.2111.06359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stability of motion and thermodynamics in charged black holes in $f(T)$ gravity

G. G. L. Nashed,
Emmanuel N. Saridakis

Abstract: We investigate the stability and thermodynamics of spherically symmetric solutions in f (T ) gravity using the perturbative approach. We consider small deviations from general relativity and we extract charged black hole solutions for two charge profiles, namely with or without a perturbative correction in the charge distribution. We examine their asymptotic behavior, we extract various torsional and curvature invariants, and we calculate the energy and the mass of the solutions. Furthermore, we study the stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Additionally, the stability analysis of the geodesic motion of particles around a BH is an important research topic in the field of gravitational physics, which plays a vital role in exploring the properties of black holes and gravity. Under different contexts of BH, people have conducted extensive research on the stability of black holes through the application of geodesic deviation equation, such as charged black holes in f (T) theory [21], rotating (anti-) de-Sitter black holes in f (R) theory [22], and non-trivial black holes [23], etc [24][25][26][27]. In this paper, we also discuss the stability of the geodesic motion of particles around black holes in the GBD gravity theory.…”
Section: Of 12mentioning
confidence: 99%
“…Additionally, the stability analysis of the geodesic motion of particles around a BH is an important research topic in the field of gravitational physics, which plays a vital role in exploring the properties of black holes and gravity. Under different contexts of BH, people have conducted extensive research on the stability of black holes through the application of geodesic deviation equation, such as charged black holes in f (T) theory [21], rotating (anti-) de-Sitter black holes in f (R) theory [22], and non-trivial black holes [23], etc [24][25][26][27]. In this paper, we also discuss the stability of the geodesic motion of particles around black holes in the GBD gravity theory.…”
Section: Of 12mentioning
confidence: 99%
“…There it has been shown that such modifications to the gravitational action may be able to naturally produce dark matter and dark energy effects [14]- [17]. Stellar structure has also been studied in some detail [18] - [26] as well as black holes [27] - [33]. A nice review of the subject may be found in [34].…”
Section: Introductionmentioning
confidence: 99%